Law and Intergenerational Relationships: Comparing Labor Case Law in the United States, Canada, and Israel. (March 2017) - Doron, Israel; Lowenstein, Ariela; Biggs, Simon
Background: In any aging society, the sociolegal construction of intergenerational relationships is of great importance. This study conducts an international comparison of a specific judicial issue: whether active labor unions have the legal right to strike for the purpose of improving the benefits given to nonactive workers (specifically, pensioners).Method: A comparative case law methodology was used. The texts of three different Supreme Court cases—in the United States, Canada, and Israel—were analyzed and compared.Findings: Despite the different legal outcomes, all three court rulings reflect a disregard of known and relevant social gerontology theories of intergenerational relationships.Conclusion: Social gerontological theories can play an important role in both understanding and shaping judicial policies and assisting the courts in choosing their sociojudicial narratives.